1994
DOI: 10.1007/bf00336709
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus type 16 associated with multifocal transitional cell carcinomas of the bladder in two transplanted patients

Abstract: This report describes two cases of rapidly progressive, multifocal transitional cell carcinomas of the bladder that developed in two patients after renal and cardiac transplantation, respectively. In both cases human papillomavirus (HPV) type 16 DNA was detected using the polymerase chain reaction DNA amplification method. To our knowledge, this HPV type has not been previously described in multifocal bladder transitional cell carcinoma in transplanted patients. Our findings suggest that HPV may play a major r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…DNA studies used to find pooled estimation of link between HPV infection and bladder cancer with estimated OR, reliability range and assigned weighting. Angliano et al, 1994, Angliano et al 3 Anwar et al, 1992, Anwar et al 5 Bryant et al, 1991, Bryant et al 8 Chan et al, 1997, Chan et al 9 Fioriti et al, 2003, Fioriti et al 13 Gazzaniga et al, 1998, Gazzaniga et al 16 Tekin et al, 1999, Tekin et al 18 Kerley et al, 1991, Kerley et al 19 LaRue et al, 1995, LaRue et al 26 Ludwing et al, 1996, Ludwig et al 31 Noel et al, 1994, Noel et al 36 Shibutani et al, 1992, Shibutani et al 39 Smetana et al, 1995, Smetana et al 40 FIG. 3.…”
Section: Discussionmentioning
confidence: 99%
“…DNA studies used to find pooled estimation of link between HPV infection and bladder cancer with estimated OR, reliability range and assigned weighting. Angliano et al, 1994, Angliano et al 3 Anwar et al, 1992, Anwar et al 5 Bryant et al, 1991, Bryant et al 8 Chan et al, 1997, Chan et al 9 Fioriti et al, 2003, Fioriti et al 13 Gazzaniga et al, 1998, Gazzaniga et al 16 Tekin et al, 1999, Tekin et al 18 Kerley et al, 1991, Kerley et al 19 LaRue et al, 1995, LaRue et al 26 Ludwing et al, 1996, Ludwig et al 31 Noel et al, 1994, Noel et al 36 Shibutani et al, 1992, Shibutani et al 39 Smetana et al, 1995, Smetana et al 40 FIG. 3.…”
Section: Discussionmentioning
confidence: 99%
“…There is lack of data to indicate a definitive association between BKV and human cancers (Noel et al, 1994;Husain et al, 2009;Abend et al, 2009;Wang et al, 2009;Roberts et al, 2008;Chen et al, 2010). Presence of polyoma virus in the biopsy specimen may mimick high grade transitional cell carcinoma (Seftel et al, 1996).…”
Section: Role Of Virus In the Carcinogenesis Of Urothelial Carcinomamentioning
confidence: 99%
“…It is remarkable that some of those authors who only found a low prevalence of HPV in bladder carcinoma [7,11,16] or reported on casual findings [33,34] identified HPV DNA in patients with immunodeficiency syn dromes. As the significance of HPV in the development of bladder cancer remains highly equivocal it has been sus pected that only in a minority of immunosuppressed patients HPV plays a decisive epidemiological role.…”
Section: Human Papillomavirus In Tissue Of Bladder and Bladder Carcinmentioning
confidence: 99%